2022
DOI: 10.1108/lthe-02-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Students’ uptake and perspectives on teacher and peer feedback on written assignments

Abstract: PurposeThe purpose of this study is to examine the uptake of peer vs. instructor feedback provided on written essays by undergraduates in a writing course at a public university in Saudi Arabia.Design/methodology/approachThis was a classroom intervention exploratory study with 16 pairs of students attending a writing class over a period of 14 weeks.FindingsAnalysis of feedback and uptake indicated that the students incorporated a high rate (85.21%) of feedback in revising their essays. The results also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…This claim is interpreted by the increase in student writing results, which can be seen from the increase in score gain during the pre-test and post-test, as well as the t-test results, which shows that the peer and teacher feedback technique using Twitter increases student writing performance. The results of this study are in line with research conducted by Maarof et al (2011), Han & Xu (2020), Alharbi & Alqefari (2022), Gonzalez-Torres & Sarango (2023), and Zou et al (2022 who found that combining the collaboration of peer feedback and teacher feedback techniques in learning writing skills is a more effective approach than using only one of these learning techniques. In addition, the presence of Twitter as a learning tool is also one of the supporting aspects of improving students' writing skills.…”
Section: Learning Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This claim is interpreted by the increase in student writing results, which can be seen from the increase in score gain during the pre-test and post-test, as well as the t-test results, which shows that the peer and teacher feedback technique using Twitter increases student writing performance. The results of this study are in line with research conducted by Maarof et al (2011), Han & Xu (2020), Alharbi & Alqefari (2022), Gonzalez-Torres & Sarango (2023), and Zou et al (2022 who found that combining the collaboration of peer feedback and teacher feedback techniques in learning writing skills is a more effective approach than using only one of these learning techniques. In addition, the presence of Twitter as a learning tool is also one of the supporting aspects of improving students' writing skills.…”
Section: Learning Resultssupporting
confidence: 91%
“…Twitter was used as a learning tool for A2-level French narrative text writing during the treatment. The flow of the treatment developed was adopted from the research of Han & Xu (2020) and Alharbi & Alqefari (2022) as follows:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaborative writing (CW) refers to two or more writers engaged in substantial interaction to compose a jointly produced text (Lunsford & Ede, 1990). Recent empirical and theoretical publications on face-to-face collaborative writing demonstrated considerable attention to the outcomes that collaborative writing produced, ranging from the effects on students' writing fluency (Pham, 2021), the value of peer reflective practices (Herder et al, 2018), how dialogic feedback is constructed in tasks (Alharbi & Alqefari, 2022). However, the present research failed to illustrate the approaches used by the collaborators to push forward the de-escalation of disagreements or potential intragroup conflict in the collaborative writing classroom.…”
Section: Introductionmentioning
confidence: 99%